Study of the Libyco-Berber inscriptions on the island of Tenerife (Palaeohispanica. Review about languages and cultures of Ancient Hispania, 2024)
This study examines seven Libyco-Berber inscriptions in Tenerife, three of which were discovered through the Inventory of Alphabetical Rock Inscriptions of the Canary Islands. It analyzes supports, contexts, and texts, identifying affected graphemes due to overlapping engravings and exploring a potential link of one inscription to a Christian depiction. It observes the script's spatial relationship with elevated points and traditional pathways, as well as its cultural connection to Berber iconographic engravings. The study of the texts uncovers grammatical elements and a dialectal phenomenon seen in Guanche toponomy. This phonetic characteristic, coupled with the potential association of an inscription with Christian themes, hints at the script's use persisting until the Spanish Conquest.
Keywords: Libyco-Berber Epigraphy; Archaeology; Rock inscriptions; Guanche; Canary Islands